PROBLEMATIKA KOMUNIKASI KELUARGA DAN PENANGGULANGANNYA Komparasi Konsep Tri Kaya Parisudha dan Gottmans Horsemen - I Made Gunarta; Ni Luh Manik Puja Dewi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
In essence, humans as social creatures cannot be separated from interaction. Everyone wants to talk, wants to express different opinions with the aim of obtaining information. This creates a process called communication. Communication was a very common thing in ancient times, even in prehistoric times. It's just that at that time communication was done in a different way, and of course communication at that time was done in a very simple way. In line with the development of time and human civilization, communication models are experiencing rapid development day by day. In the beginning, before the discovery of electronic media as a source of communication, people communicated by making simple tools made from improvised materials and tools such as gongs. Some people in the past and perhaps even today know of a form of communication through the sound of a gong. Through the sound of the gong, it is symbolized as a symbol of past communication, and most of it is one-sided, so it can be said that there are not many components involved in communication. This process only involves one person or group of people as the communicator and another party as the listener. It was different when the reform era began and various innovations emerged from both communication experts and practitioners. Communication is a need and an important means to get to know yourself and others. Who we are and how we interact with others is discovered through communication. Without us realizing it, we carry out these communication activities in every activity of our lives. Through communication we will understand ourselves and others so that we can develop our self-understanding in family and community relationships and develop shared concepts in the social environment. In fact, we can find small communication groups that often occur every day in the family environment in husband-wife relationships. Even though communication always occurs in every interaction in human life, not every communication that occurs can lead to understanding. And it is not uncommon for every communication carried out to give rise to debates and discrepancies between each other due to differences in understanding of each communication participant.